PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN KIMIA DI MADRASAH ALIYAH - Ramli Abdullah (Lantanida Journal, 2017)
Cooperative learning using the jigsaw type is a learning strategy that can foster effective communication, create an active learning environment, and can provide satisfactory learning outcomes. Many studies show that peer teaching is more effective than teacher teaching, the application of jigsaw type cooperative learning on the subject matter can improve student activity and learning outcomes, can also encourage good communication and high social interaction Fellow students. That is expected from the learning activity is the occurrence of student activities in learning materials chemistry subjects during the learning process took place by applying cooperative learning model type jigsaw classified as very good, the occurrence of student responses in learning subject matter Chemistry during the learning process took place by applying the model Jigsaw type cooperative learning is categorized as very good, and the achievement of learning achievement of students in learning materials of reasoning subject of Chemistry with the application of cooperative learning model of jigsaw type happened improvement of learning result belonging to good category.